Reaching win-win state of mind in games, formulation and solution - Larbani, Moussa; Yu, Po Lung (Yokohama Publisher, 2009)
Human psychology determines his/her action and behavior. This fact has not been fully incorporated in game theory. This paper intends to incorporate human psychology in formulating games as people play them. Using Habitual Domains and Markov chains theory, we present a new model for describing the evolution of the states of mind of players over time, the two person second order game. We introduce the concept of focal mind profile as well as the solution concept of win-win mind profile. Under some suitable assumptions, the restructuring game to reach a win-win mind profile can be formulated into a discrete optimal control problem. We illustrate the formulation with an example.